Political competition and local government debt: implications for human development: A case study of Eastern Cape municipalities - Matapuri, Fadzai Valerie (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
South African Municipalities are currently in a precarious financial situation. The financial distress has intensified so much that local governments are on the brink of collapse. Municipalities in South Africa currently owe over 35.5 billion rands. Reports from the Auditor-General of South Africa portrayed a grim picture of the state of financial affairs in municipalities; only 33 municipalities out of 278 had received a clean audit, with over 30 billion rands in expenditure declared irregular. The report further revealed that there were numerous cases of non-compliance with key legislation in municipalities. The poor financial audits across the country have stressed the severe lack of accountability, government issues and political turmoil. Due to this state of affairs, municipalities cannot deliver services such as sanitation, electricity, and water. As a result, many service delivery protests have occurred over the years. Political factors have been highlighted as the leading cause of these local government woes. This study aims to investigate the relationship between political competition and local government debt and its effect on human development in Eastern Cape municipalities. The study used a panel data set for 32 municipalities and electoral data from 2009 to 2016. The panel vector autoregression model, generalized least squares, fixed and random effects methods were used to investigate the relationship between political competition and local government debt. The study found a positive unidirectional relationship between political competition and local debt. This was found using the normalized Herfindahl index, debt to asset, tress index, human development index, population and poverty variables. Moreover, estimated results showed that local governments in the eastern cape were characterised by a political monopoly that, in turn, increased local government debt through growth-hindering policies adopted by political leaders. Resulting in economic concentration, which hinders local economic growth and human development.
Keywords: Local government -- South Africa -- Eastern Cape; Municipal finance -- South Africa -- Eastern Cape; Public administration -- South Africa -- Eastern Cape; Municipal services -- South Africa -- Eastern Cape; Electoral competition; Human development